2019
DOI: 10.4102/hsag.v24i0.1051
|View full text |Cite
|
Sign up to set email alerts
|

Describing medicine therapy management of type 2 diabetes mellitus at primary health care facilities in Cape Town

Abstract: To describe the use of glycated haemoglobin (HbA1c) and fasting plasma glucose results in guiding treatment changes in patients with type 2 diabetes mellitus.Setting: Public sector primary health care facilities in the Cape Town Metropolitan Region in South Africa.Method: Retrospective, descriptive study design was employed. Data for an 18-month period were collected during 2014 and 2015. Data were collected from patient medical records and included baseline demographics, laboratory monitoring tests and the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The plausible explanation for the high HbA1c among COVID-19 cases with HIV could be more severe inflammatory process and more intense coagulation disorder associated with poor prognosis [ 45 ]. Another explanation could be the high HbA1c found in public sector primary health care facilities in Cape Town as a study showed 78.9% of type 2 diabetes mellitus patients had HbA1c outside of the target range [ 46 ]. As high HbA1c may not be a reliable biomarker in this context, our findings were focused on the neutrophils and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…The plausible explanation for the high HbA1c among COVID-19 cases with HIV could be more severe inflammatory process and more intense coagulation disorder associated with poor prognosis [ 45 ]. Another explanation could be the high HbA1c found in public sector primary health care facilities in Cape Town as a study showed 78.9% of type 2 diabetes mellitus patients had HbA1c outside of the target range [ 46 ]. As high HbA1c may not be a reliable biomarker in this context, our findings were focused on the neutrophils and CRP.…”
Section: Discussionmentioning
confidence: 99%
“…The DISCOVER study was selected from a literature search that identified 6 publications that described type 2 diabetes management in South Africa [ 9 , 19 - 23 ]. The South African cohort of the DISCOVER study was chosen since it included patients from the private sector and had the necessary HbA 1c data to assess diabetes evolution [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization (WHO) also declared metformin a model drug for diabetes due to its efficiency [5], and it is the most consumed pharmaceutical drug due to the highest number of diabetes worldwide [6]. The international diabetes federation (IDF) also states that almost 2.3 million metformin prescriptions are made annually [7]. According to toxicological studies, metformin is a potential endocrine disruptor [8], and hence, the stability of this drug in water shows the need for its removal [9].…”
Section: Introductionmentioning
confidence: 99%